Analisis Kelayakan Usaha Industri Rumahan Kecap Cap Bulan Di Kota Palembang - Wintari Mandala; Novia Ambar Sari (Jurnal Prodi Agribisnis, 2022)
This study aims to determine the business feasibility of the Cap Bulan soy sauce home industry business. This research was conducted on a home industry business making soy sauce located in Palembang City. The method in this study is by interviewing directly by the author to the source. Data collection was carried out in June 2022 for 2 days. In collecting primary data, data was obtained from the owner of the Jaya Kecap Cap Bulan Business Industry and the employees who worked there. The data collection technique carried out is by means of direct interviews, in-depth interviews and observations. Such data collection techniques are used to collect primary data. As for secondary data, data collection techniques are carried out by means of literature studies. Financial analysis and feasibility of fish sauce processing business according to the assumptions used is feasible to be carried out with a Net B/C Ratio of 1.98, and NPV of Rp 2,830,887,867.61. It is known that the Ketchup Cap Bulan home industry business is still feasible to run.